Android application of quick organizer - Baxi, Poonam Satish (Kansas State University, 2012)
The aim of this project is to develop an Android application for managing and organizing daily activities. Mobile application development is a growing trend in computer industry. Lot of desktop applications is [i.e. are] now becoming available as mobile applications with increasing demand in market. Android is one of the most popular platforms in mobile technology and gives lot of space for creative development as it is open source. There are various discussion forums and official Android development support websites that encourages mobile and tablet application development. The Quick Organizer application provides three main features for managing and organizing everyday tasks. 1. Calendar with smooth navigation buttons and flexible layout to view all calendar events. This calendar synchronizes with Google calendar and calendar application in Android device and allows user to create events in all the user calendar accounts. 2. Notes management for creating new note, viewing all notes for current month and search notes for the user account that synchronizes with the Ever Notes application. 3. Tasks management to create daily to-do lists with deadline for every task. The user can see all the tasks created with clear demarcation between complete and incomplete tasks with help of strike-out tasks when completed.
Keywords: Android; Calendar application; Ever Notes application; Task management; Computer Science (0984)